Beltanelliformis konovalovi sp. nov. From the Terminal Neoproterozoic of Central Urals: Taphonomic and Ecological Implications - Kolesnikov, Anton (Frontiers in Earth Science, 2022)
The siliciclastic succession of the Ediacaran Chernyi Kamen Formation in the Central Urals of Russia contains a rich complex of Ediacaran fossils that represent in situ benthic populations buried in life position. The present work reports Beltanelliformis konovalovi sp. nov. found as a paleocommunity of organisms and studied for their morphology and spatial distribution. Unlike the type species (B. brunsae), new fossils are preserved within fine-grained sandstone beds as three-dimensional pancake-like or flattened discoidal single, paired, or occasionally aggregated bodies with an ultra-thin rim. Statistical analysis shows significant predominance of small individuals in the paleocommunity, which in turn manifests different spatial distribution in comparison with larger ones. In addition, the studied paleocommunity exhibits patterns of self-organization in extremely shallow marine environment and adaption to periodic desiccation. These results provide quantitative support for the more complex ecology of Beltanelliformis and also expand the range of taphonomic possibilities of macroscopic life in the terminal Neoproterozoic.